The restoration of celia fairchild eaudiobook A novel. - Bostwick, Marie (2021)
"The Restoration of Celia Fairchild is wise, witty, and utterly compelling." —Jane Green, New York Times bestselling author of The Friends We Keep Evvie Drake Starts Over meets The Friday Night Knitting Club in this wise and witty novel about a fired advice columnist who discovers lost and found family members in Charleston, by the New York Times bestselling author of The Second Sister. Celia Fairchild, known as advice columnist 'Dear Calpurnia', has insight into everybody's problems – except her own. Still bruised by the end of a marriage she thought was her last chance to create a family, Celia receives an unexpected answer to a "Dear Birthmother" letter. Celia throws herself into proving she's a perfect adoptive mother material – with a stable home and income – only to lose her job. Her one option: sell the Charleston house left to her by her recently departed, estranged Aunt Calpurnia. Arriving in Charleston, Celia learns that Calpurnia had become a hoarder, the house is a wreck, and selling it will require a drastic, rapid makeover. The task of renovation seems overwhelming and risky. But with the help of new neighbors, old friends, and an unlikely sisterhood of strong, creative women who need her as much as she needs them, Celia knits together the truth about her estranged family — and about herself. The Restoration of Celia Fairchild is an unforgettable novel of secrets revealed, laughter released, creativity rediscovered, and waves of wisdom by a writer Robyn Carr calls ""my go-to author for feel-good novels."